A framework for evaluating environmental commitment tracking programs in state departments of transportation - Fillion, Andrew Christopher, author; Ozbek, Mehmet, advisor; Clevenger, Caroline, committee member; Taylor, Peter, committee member (Colorado State University. Libraries, 2011)
Environmental tracking systems (ETSs) are used by state Departments of Transportation (DOTs) as well as by Federal agencies to track environmental commitments on construction projects from the project development stage through design, construction, and project completion. In this study a framework is developed that any state DOT can use to evaluate existing ETSs implemented by other state DOTs. This framework will allow that state DOT to identify the system that best meets its needs with the ultimate purpose of adopting that system. The framework's main function will be to identify and prioritize the features that a state DOT is looking for in an ETS, to evaluate existing ETSs used by other state DOTs with respect to those features, and to provide a final recommendation on which ETS should be adopted by that state DOT. The developed framework was implemented at the Colorado Department of Transportation (CDOT). The findings and recommendations for that implementation example are also included in this study.
Keywords: commitment; DOTs; environmental; systems; tracking; transportation